Engineering Plants for Geminivirus Resistance with CRISPR/Cas9 System. (April 2016) - Zaidi, Syed Shan-e-Ali; Mansoor, Shahid; Ali, Zahir; Tashkandi, Manal; Mahfouz, Magdy M.
Abstract : The CRISPR/Cas9 system is an efficient genome-editing platform for diverse eukaryotic species, including plants. Recent work harnessed CRISPR/Cas9 technology to engineer resistance to geminiviruses. Here, we discuss opportunities, emerging developments, and potential pitfalls for using this technology to engineer resistance against single and multiple geminivirus infections in plants.